1977
DOI: 10.1097/00004032-197712000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Measurements of 222Rn Concentrations in Water With a Commercial Liquid Scintillation Counter

Abstract: A technique is described by which concentrations of 222Rn in water as low as 10 pCi/l can be determined by a 40-min count of a 10-ml sample. Preparation time is about 1 min/sample, and no special equipment is required other than access to a commercial liquid scintillation system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

1987
1987
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(40 citation statements)
references
References 0 publications
0
40
0
Order By: Relevance
“…A second possibility is interaction of the gas phase 222 Rn and daughters with the liquid scintillation cocktail. Prichard and Gesell (1977) assumed 25% of the gas phase radionuclides contributed to the observed count rate by interacting at the cocktail-air meniscus. Murase et al (1989) reported a counting efficiency of 42% for radon and its daughters in an empty LS vial as a result of air luminescence.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…A second possibility is interaction of the gas phase 222 Rn and daughters with the liquid scintillation cocktail. Prichard and Gesell (1977) assumed 25% of the gas phase radionuclides contributed to the observed count rate by interacting at the cocktail-air meniscus. Murase et al (1989) reported a counting efficiency of 42% for radon and its daughters in an empty LS vial as a result of air luminescence.…”
Section: Methodsmentioning
confidence: 99%
“…The magnitude of the aqueous-organic radon partition coefficient K is dependent on the base solvent used in the scintillation cocktail. Reported values range from 45 for toluene based scintillation cocktails (Prichard and Gesell 1977) to 23 for a high efficiency mineral oil (long chained aliphatic hydrocarbons and psuedocumene) cocktail (Lowery 1991). A value of 32 at approximately 20 ºC was measured in our laboratory for an 'environmentally friendly' scintillation cocktail based on diisoproplynaphthalene (Cantaloub et al 1997).…”
Section: Background and Theorymentioning
confidence: 99%
See 2 more Smart Citations
“…(2b). The water samples and a Revigator water sample were analyzed using a liquid scintillation counter (LSC) (Packard Tri-Carb 2750TR, Ramsey, Mn, USA) for 222 Rn measurements [13]. The LSC also measured 222 Rn concentrations with a PM tube.…”
Section: Water Samplesmentioning
confidence: 99%